(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the history of the tragic events marked by the history of the country, including the history of the Al-Farabi Kazakh National University, mass political repression of the 1920-1950s of the XX century have a special place. The repressive soviet state policy that began in the 1920s and by the 1930s of XX century was a fairly well functioning and smoothly operating mechanism. Its extremely intensive work was marked when the cult of the personality of Stalin as «the leader of all nations» in the country was finally established. The Soviet state became essentially a testing ground for conducting various socio-economic and political experiments «in the Stalinist way». The contradiction between the proclaimed official power «socialism in the country» and regional reality has reached its critical point. The cause of the conflict between the government and the Kazakh intellectuals, as well as the exact number of victims in that period have not been fully studied to this day. The object of research are public situation in Kazakhstan, the sources of controversy between the Soviet government and Kazakhstani intellectuals, the causes of mass sexual repression and the effects of such phenomena. Representatives of the Kazakh intellectuals in their writings consider the ideas and political origins of national law, including critical issues related to the directive methods of the USSR regime. The special attention was given to political persecution by the state, which in turn caused political harassment from the government. The comparative analysis of the documentary bases of this period made it possible to clarify the general trends and patterns of Kazakh society development in the 1930s, to analyze the logic of the actions of the repressive mechanism. Key words: political regime, repression, conflict, the Kazakh intellectuals, ideological control, repressive policy.